Design of high precision microscope objective for optical-fiber-fusion-splicing based on apochromatic theory - Zhang, Xingyun; Gao, Yanhong; Zhao, Shijia; Ji, Yiqun (Oficyna Wydawnicza Politechniki Wrocławskiej, 2025)
With the rapid development of optical fiber communication technology, the requirement for high-quality splicing has also increased. The accuracy of optical fiber alignment is the most crucial factor in determining splicing quality. The imaging quality of the microscope objective and the accuracy of the optical fiber alignment algorithm together determine the accuracy of optical fiber alignment. This paper proposes a new alignment method based on the black line at the interface between optical fiber core and cladding. The imaging characteristics of the black line are analyzed, and the initial structure of the microscope objective is deduced based on the theory of apochromatism, and finally a high-precision optical fiber fusion splicing microscope objective with a waveband from 460 to 660 nm is designed. An experimental device is set up to obtain optical fiber images, and the results indicate that the microscope objective plays a significant role in magnifying black lines. The horizontal and vertical offsets of optical fiber can be accurately identified through image processing. This paper considers the lens design theory and feature recognition algorithm comprehensively to improve the accuracy of optical fiber alignment, ultimately achieving high-quality optical fiber fusion splicing.
Optica Applicata, Vol. 55, 2025, nr 2, s. 143-156
Optica Applicata is an international journal, published in a non-periodical form in the years 1971-1973 and quarterly since 1973. From the beginning of the year 2008, Optica Applicata is an Open Access journal available online via the Internet, with free access to the full text of articles serving the best interests of the scientific community. The journal is abstracted and indexed in: Chemical Abstracts, Compendex, Current Contents, Inspec, Referativnyj Zhurnal, SCI Expanded, Scopus, Ulrich’s Periodicals Directory
http://opticaapplicata.pwr.edu.pl/
Keywords: optyka; optical-fiber-fusion-splicing; microscopic imaging; optical design; imaging processing